Anatomical characteristics of cocoa plant roots as affected by the levels of calcium fertilization - Sutan Tarmizi Lubis; Eka Tarwaca Susila Putra; Budiastuti Kurniasih (Jurnal Ilmu Pertanian, 2022)
Cocoa plant (Theobroma cacao L.) is one of good annual crops grown in Indonesia. The disadvantages and advantages of Ca in plants can affect morphology and anatomy in plants. This research aimed to identify the effect of Ca on the anatomical performance of the roots of cocoa plants and determine the optimal dose of Ca for the anatomical characteristics of the roots of cocoa plant. The research was conducted at the cocoa plantation owned by PT. Pagilaran at North Segayung Production Unit, Tulis Subdistrict, Batang Regency, Central Java, in October 2019 – February 2021. The observation of root anatomy was carried out by making preparations, and the plant roots were taken destructively and sliced transversely. The field experiment was arranged using a single factor randomized complete block design. The treatments consisted of without fertilizer application and calcium fertilization at a dose of 100 g/tree/year, 200 g/tree/year, 300 g/tree/year, and 400 g/tree/year. The cocoa clone used was clone RCC 71. The results showed that an increase in the dose of CaCl2 fertilizer up to 400 g/tree/year was generally followed by an increase in the size of the xylem and phloem diameters, the thickness of the cork layer, the thickness of secondary cortex, and the diameter of the stele. The quadratic effect of the dose of CaCl2 fertilizer was observed only on the thickness of the root cambium tissues. Thus, it is necessary to conduct further research to determine the optimal dose of Ca fertilizer for the anatomical characteristics of cocoa roots.